Negotiating urban life: Place, community resilience, and lived experience in Northern Medan - Lubis, Endar Sutan; Harahap, R Hamdani; Kusmanto, Heri; Ridho, Hatta (Research Journal in Advanced Humanities, 2026)
Urban life is shaped not only by infrastructure and planning but also by the meanings that people attach to the places they inhabit and the everyday practices through which they negotiate opportunities and constraints. This article examines how residents of Northern Medan experience and construct urban life amid spatial inequality, environmental vulnerability, and uneven urban development. Rather than conceptualizing urban livability as a technical outcome of planning interventions, the study approaches it as a lived experience produced through the interaction of place, community relationships, and everyday acts of resilience. Focusing on the districts of Belawan, Labuhan, Marelan, and Deli, the research employs a mixed-methods design combining household surveys, semi-structured interviews, and community narratives to explore both measurable dimensions of urban conditions and residents' interpretations of belonging, security, and quality of life. The findings reveal that urban life is negotiated through localized social practices that sustain community cohesion despite persistent challenges, including recurrent flooding, inadequate infrastructure, environmental degradation, and socio-economic disparities. Residents draw upon neighborhood solidarity, shared cultural practices, informal support networks, and collective adaptation to create meaningful forms of belonging and resilience that extend beyond material conditions. While spatial inequalities continue to shape everyday experiences, local communities actively reinterpret and reconstruct urban space through social relationships, cultural identity, and place-based knowledge. These findings suggest that urban livability is not merely a function of physical development but a socially and culturally produced condition emerging from the continuous negotiation between people, place, and structural constraints. By centering lived experience and everyday urban practices, this article contributes to urban humanities scholarship by demonstrating how community resilience and place-making shape the human experience of rapidly transforming cities in the Global South. It argues that understanding cities requires greater attention to the cultural meanings, social relationships, and everyday practices through which residents create dignified and livable urban lives.